Auditory sentence comprehension in children with cochlear implants after simple visual discrimination training with specific auditory-visual consequences - das Neves, Anderson Jonas [UNESP]; Almeida-Verdu, Ana Claudia Moreira [UNESP]; do Nascimento Silva, Leandra Tabanez; Moret, Adriane Lima Mortari; das Graças de Souza, Deisy (Springer Nature, 2020)
The present study evaluated the effects of simple discrimination training with specific consequences on auditory comprehension in children with cochlear implants (CIs). Demonstration of auditory comprehension was based on derived conditional relations and the formation of equivalence relations. Participants learned two sets of three simple visual discriminations in which the positive stimulus (S+) was a written pseudo-sentence (C1, C2, or C3) or a compound abstract picture (D1, D2, or D3), displayed in the correct orientation. Each trial presented the S+ simultaneously with two S- which were the same sentence or picture as the positive stimulus but were displayed in either an upside-down or an inverse orientation. Correct responses were followed by specific consequences with two components presented simultaneously: a dictated pseudo-sentence (A) and a representative picture (B). Probes of arbitrary matching to sample assessed derived auditory-visual (AB, AC, and AD) and visual-visual (BC, CB, BD, DB, CD, and DC) conditional relations. All three participants learned the simple discriminations; two of them showed derived conditional relations, demonstrating the formation of three ABCD classes. The present study replicated and extended previous results on sentence learning in children with CIs, suggesting the simple discrimination training with specific consequences as an efficient procedure to generate auditory-visual and symbolic relations in this population.
Keywords: Children; Cochlear implant; Sentences; Specific consequences; Stimulus equivalence